Analisis Penerapan Enterprise Resource Planning (ERP) Pada PT Sinar Sosro Palembang - Ria Andika; Diana Diana (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
PT. Sinar Sosro which is the first ready to drink bottled company in Indonesia and in the world. In developing its business, PT. Sinar Sosro has distributed sales throughout the archipelago, through sales branch offices spread throughout the archipelago. PT. Sinar Sosro in its company management has implemented the Enterprise Resource Planning System, the ERP system built by Sosro's management allows access to data from Sosro's branch offices. Functional area at PT. Sinar Sosro covers: Sales and marketing, Manufacturing, Finance, Accounting, Logistics, Distribution, Inventory, Invoice. In the grip of this functional area, PT. Sinar Sosro uses SAP as its ERP program. The distribution system is capable of handling the company's manufacturing, logistics, inventory, shipping, invoicing, and accounting processes. This system helps control business activities such as sales, delivery, production, inventory management, quality management, and human resources. The modules used in SAP are inventory management, plant maintenance, production, finance and accounting, human resource management.